Perlindungan Hukum bagi Pelaku Usaha Mikro, Kecil, dan Menengah (UMKM) dalam Persaingan Usaha - Rahmawati, Anisa; Septiana, Findi; Ananda, Melisa; Aulia, Luluk (SJEE (Scientific Journals of Economic Education), 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in supporting the national economy, particularly in creating jobs and driving people-based economic growth. However, MSMEs often face various challenges in business competition, particularly due to the imbalance in economic power compared to large businesses. This situation has the potential to lead to unfair business competition practices that are detrimental to MSMEs. Therefore, legal protection for MSMEs is a fundamental need to create a fair and sustainable business climate. This study aims to analyze the forms of legal protection for MSMEs in business competition and assess the effectiveness of applicable legal regulations in Indonesia. The research method used is normative legal research with a statutory and conceptual approach. The results show that the legal framework for MSME protection is in place, but its implementation still faces obstacles, particularly in aspects of law enforcement, supervision, and legal literacy of MSME actors. Strengthening the role of the government and competition supervisory agencies is necessary for optimal legal protection for MSMEs.